Siege and storm - Bardugo, Leigh (Bardugo, Leigh. Grisha trilogy, 2013)
Hunted across the True Sea and haunted by the lives she took on the Fold, Alina must try to make a life with Mal in an unfamiliar land, all while keeping her identity as the Sun Summoner a secret.